2009
DOI: 10.1128/jvi.00286-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Monoclonal Antibodies against West Nile Virus Induced by Natural Infection Neutralize at a Postattachment Step

Abstract: West Nile virus (WNV) is a neurotropic flavivirus that is now a primary cause of epidemic encephalitis inWNV cycles in nature between several species of birds and Culex mosquitoes, with humans and other mammals as deadend hosts (25, 62). Infection causes syndromes ranging from a mild febrile illness to severe encephalitis and death (13, 72). WNV has spread globally and causes outbreaks with thousands of severe human cases annually in the United States. An age of greater than 55 years, a compromised immune stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
105
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 89 publications
(137 reference statements)
10
105
0
Order By: Relevance
“…Little to no conservation of the identified epitope residues was observed among other flaviviruses (Fig. S4), consistent with the strict type-specificity of CR4354 for WNV (21).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…Little to no conservation of the identified epitope residues was observed among other flaviviruses (Fig. S4), consistent with the strict type-specificity of CR4354 for WNV (21).…”
Section: Resultssupporting
confidence: 53%
“…2 and 3). This is consistent with the inability of CR4354 to bind to recombinant, soluble E ectodomain or recognize virus particles at low pH, which have undergone a conformational change (21). Although the epitope spreads over two molecules, weak binding of a single E molecule by CR4354 should be considered, at the least for the largest contact region on a single E molecule (DI and DI-II interface).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The amino acid differences between the vaccine strains and the GI strains did not exceed 2.4 %, indicating that the difference may not influence the efficacy of the vaccines. Previous studies have identified individual residues within the E protein that are related to the recognition of JEV by neutralizing antibodies (Crill & Chang, 2004;Goncalvez et al, 2008;Kobayashi et al, 1985;Morita et al, 2001;Vogt et al, 2009;Wu et al, 2003). Although the sequence variation between the vaccine strains and GV strains do not correspond to epitope residues, only a limited number of residues could be responsible for the decreased neutralization ability of the vaccines against GV strains.…”
Section: Discussionmentioning
confidence: 99%